Mortality from cerebrovascular diseases in Ukraine - Pedachenko, Eugene; Nikiforova, Anna; Sapon, Nikolay; Huk, Andriy (Ukrainian Neurosurgical Journal, 2016)
Objective. To analyse the dynamics, gender, age, and geographical peculiarities of cerebrovascular disease (CVD) mortality in Ukraine, to estimate the indicator for the coming years. Materials and methods. A retrospective CVD mortality study was conducted in Ukraine. Mortality database (MDB) of the World Health Organization (WHO) and the data of the Ministry of Health of Ukraine (MoH) were used as the starting material. Time series analysis and regression analysis, hazard ratio (HR) were used. Results. From 1991 to 2012, CVD mortality decreased by 7.2% (from 220.4 to 204.6 per 100,000 population). CVD mortality rate is close to 0 at the age of 0 to 29 years, it exponentially increases with growing-up and aging of the population, and reaches its maximum at the age of 75 to 90 years (181 deaths per 10,000 men and 178 – in women). It was found that 99% of CVD deaths were at the age of over 45 years, 90% – over 60 years, 59% – over 75 years. Based on the mortality rates in 2012, at the time of the birth, CVD death risk in men is 0.18% (of 10,000 boys born, 18 will die of CVD at some point of life), in women – 0.23% (of 10,000 girls born, 23 will die of CVD at some point of life). The population of men aged 15 to 74 years, CVD death risk is 1.7-2.6 times higher than in women of the same age. At the age of 0 to 14 and from 75 to 90 years, parity is observed. At the age of 45 to 90 years, men and women have an equal CVD death risk. The essential heterogeneity of CVD mortality was revealed in different regions of Ukraine – the difference between the highest (472.1) and the lowest (64.6) value is 407.5 (630%). A strong highly significant inverse correlation was established between the value of health care (HC) costs and CVD mortality in Ukraine (r = -0.72, p = 0.00). In turn, the value of HC costs depends on GDP (r = 0.99, p = 0.00). By 2020, the estimated CVD mortality in Ukraine is 217-225 per 100,000 population. Conclusions. Over the period studied, Ukraine has a consistently high CVD mortality rate with low decline. In women, CVD mortality is higher than in men, but in some age periods, the situation is reversed. In different regions of Ukraine, mortality varies considerably, in the south-eastern regions, the value is extremely high. A strong highly significant inverse correlation between the value of HC costs and CVD mortality in Ukraine indicates that in the next 5 years a significant reduction in CVD mortality rate is not expected.